2021
DOI: 10.21873/cgp.20294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wild Yam Root (Dioscorea villosa) Extract on the Gene Expression Profile of Triple-negative Breast Cancer Cells

Abstract: Background/Aim: Wild yam extract [Dioscorea villosa, (WYE)] is consistently lethal at low IC 50 s across diverse cancer-lines in vitro. Unlike traditional anti-cancer botanicals, WYE contains detergent saponins which reduce oil-water interfacial tensions causing disintegration of lipid membranes and causing cell lysis, creating an interfering variable. Here, we evaluate WYE at sub-lethal concentrations in MDA-MB-231 triple-negative breast cancer (TNBC) cells. Materials and Methods: Quantification of saponins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Natural resources such as plants have long been considered as a source of chemotherapeutic or chemopreventive agents against cancer. However, due to the increasing resistance of certain tumors and the severe side effects of conventional chemotherapy, new pharmacological molecules are needed. In recent decades, advances in cancer molecular biology have identified several biological compounds capable of inhibiting cancer cell growth with improved efficacy and selectivity. Structural diversity and associated synergistic effects, high efficiency, availability, and excellent biocompatibility are the advantages of plants as medicinal resources. Traditional plants contain phytochemical compounds, which are mainly secondary metabolites used by plants to ensure their survival and fertility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural resources such as plants have long been considered as a source of chemotherapeutic or chemopreventive agents against cancer. However, due to the increasing resistance of certain tumors and the severe side effects of conventional chemotherapy, new pharmacological molecules are needed. In recent decades, advances in cancer molecular biology have identified several biological compounds capable of inhibiting cancer cell growth with improved efficacy and selectivity. Structural diversity and associated synergistic effects, high efficiency, availability, and excellent biocompatibility are the advantages of plants as medicinal resources. Traditional plants contain phytochemical compounds, which are mainly secondary metabolites used by plants to ensure their survival and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, much attention has been paid to the antitumor effect of saponins, and several publications have appeared. , Some possible reasons for the antitumor effect of saponins are the formation of pores in cell membranes and thus increased permeabilization, induction of apoptosis, inhibition of angiogenesis and metastasis, and reduction of drug efflux . Although many studies have shown that saponins damage tumors rather than attack normal organs, their use as antitumor agents in clinical trials is a major obstacle because of their high organ toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…In January 2023, an extensive search of the world's literature was performed for studies dated 1999 forward, and new data were found. [4][5][6][7][8][9] Notable findings include 2 short-term oral toxicity studies and a 13-week oral toxicity study in which the no-observed-adverse-effect-level (NOAEL) for rats of both sexes was determined to be the maximum received dose of 5000 mg/kg/d. Additionally, studies demonstrating the potential cytotoxicity of Dioscorea villosa (wild yam) root extract against breast cancer cell lines, a study of anti-inflammatory effects, and a clinical study in which no significant side effects or metabolic/endocrinal changes were seen in healthy premenopausal women following 3 mo of topical application of wild yam cream, were found.…”
mentioning
confidence: 99%